Phase separation of Polycomb-repressive complex 1 is governed by a charged disordered region of CBX2 - Plys, Aaron J; Davis, Christopher P; Kim, Jongmin; Rizki, Gizem; Keenen, Madeline M; Marr, Sharon K; Kingston, Robert E (Genes & development, 2019)
Mammalian development requires effective mechanisms to repress genes whose expression would generate inappropriately specified cells. The Polycomb-repressive complex 1 (PRC1) family complexes are central to maintaining this repression. These include a set of canonical PRC1 complexes, each of which contains four core proteins, including one from the CBX family. These complexes have been shown previously to reside in membraneless organelles called Polycomb bodies, leading to speculation that canonical PRC1 might be found in a separate phase from the rest of the nucleus. We show here that reconstituted PRC1 readily phase-separates into droplets in vitro at low concentrations and physiological salt conditions. This behavior is driven by the CBX2 subunit. Point mutations in an internal domain of eliminate phase separation. These same point mutations eliminate the formation of puncta in cells and have been shown previously to eliminate nucleosome compaction in vitro and generate axial patterning defects in mice. Thus, the domain of CBX2 that is important for phase separation is the same domain shown previously to be important for chromatin compaction and proper development, raising the possibility of a mechanistic or evolutionary link between these activities.